ANALYSIS OF MARKETING MIX (8P) AND CUSTOMER SATISFACTION FOR BRAND AWARENESS IN SANTIKA HOTEL JABODETABEK AREA - ., Sofiani (Journal of Business And Entrepreneurship, 2021)
Higher brand awareness value and brand name can enhance its potential choosing by the customer. It also leads to higher loyalty and higher inclination of customers to pay more and higher purchase by the customer and lower firms' susceptibility in a competitive market. This study aimed to analyze the effect of Marketing Mix 8P (product, price, place, promotion, people, physical evidence, productivity and quality, process) and customer satisfaction for brand awareness in the Santika Hotel Jabodetabek. This study used primary data obtained from field research with Santika Hotel Jabodetabek customers and secondary data. To collect and analyze data, statistical regression analysis was used to determine patterns of relationships that reveal independent variables' influence on the dependent variable. Based on the regression analysis results, the product, price, place, promotion, people, physical evidence, productivity and quality, process, and customer satisfaction simultaneously have a significant impact on brand awareness. Based on the results of hypothesis analysis and testing of field data, simultaneously product, price, place, promotion, people, physical evidence, productivity and quality, process and customer satisfaction have a significant influence on brand awareness where the effect given by independent variables to the dependent variable is positive.